Detection and measurement of oral malodour in periodontitis patients - John Mathew; Vandana K (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND &OBJECTIVES : Malodour has been correlated with the concentration of volatile sulphur compounds produced in the oral cavity by metabolic activity of bacteria colonizing the periodontal sites and the dorsum of the tongue. The aim of this study was to detect malodour in mouth air organoleptically and using a portable sulphide monitor and to correlate it with the clinical parameters, halitosis linked toxins and BANA, using tongue and subgingival plaque samples. The halitosis grading is also correlated with the microbial colonies of the subgingival plaque sample. METHODS : 20 patients with chronic periodontitis with 5-7 mm pocket depth, radiographic evidence of bone loss and presence of oral malodour participated in this study. Assessment of mouth air was done organoleptically and by using a portable sulphide monitor. The clinical parameter, plaque index (PI), gingival index (GI), gingival bleeding index (BI), were obtained from all the areas. Samples for BANA and to detect halitosis linked toxins were taken from the dorsal surface of the tongue and periodontal pockets ranging 5-7 mm. Halitosis related microbial colonies were identified using anaerobic culturing from the subgingival plaque. RESULTS : The scores of PI, GI, BI and sample that tested positive for halitosis linked toxins and with the halitosis grading were not significant. The presence of tongue coating and the halitosis grading and toxin levels were significant. BANA has shown to be non contributory due to technical problems. Anaerobic culture has shown to identify Streptococcus, Bacteroides, Fusobacterium, Porphyromonas and Prevotella colonies. INTERPRETATION &CONCLUSION : The results confirmed that there was no correlation between the clinical parameters, halitosis linked toxins and halitosis grading. The microbial colonies have shown to correlate with the presence of oral malodour.